Realizing high-power and high-capacity zinc/sodium metal anodes through interfacial chemistry regulation - Zhen Hou (Nature Portfolio, 2021)
Zinc metal anodes suffer from severe dendrites’ growth. Herewith authors construct electrically conductive and zincophilic tin coating on separator to suppress dendrites initiation and eliminate the inevitably formed dendrites.